Selenium and Natural Zeolite Clinoptilolite Supplementation Increases Antioxidative Status and Immune Response in Growing Pigs - Šperanda, Tomislav; Pavić, Valentina; Lončarić, Zdenko; Šperanda, Marcela; Popović, Maja; Gantner, Vesna; Ðidara, Mislav (Frontiers in Veterinary Science, 2021)
Selenium (Se), an essential trace element for human and animal health, is covalently incorporated into amino acids, acts as a cofactor for antioxidant enzymes, and is involved in the maintenance of the immune system. The main goal of this investigation was to show the effect of Se supplementation, at levels slightly higher than the recommended values, combined with natural zeolite clinoptilolite on Se deposition in tissues (muscle and liver) and on the immune and antioxidative status of supplemented growing pigs. The experiment was carried out during a 98 d period on 60 pigs. Pigs were fed a standard feed mixture based on corn and soybean and were divided into four groups, according to the level of dietary selenium supplementation as follows: C-0.3 mg/kg DM organic Se, E1-0.5 mg/kg DM sodium selenite, E2-0.5 mg/kg DM organic selenium; E3-0.5 mg/kg DM organic Se+0.2% zeolite. Higher (P < 0.05) selenium concentrations were determined in the muscle and liver in growing pigs fed with higher organic Se in combination with zeolite compared to the lower organic Se concentration. Addition of organic Se increased (P < 0.05) Se deposition in muscle and liver compared to the equal amount of inorganic Se (E2 vs. E1). Higher organic Se in combination with natural zeolite addition increases (P < 0.05) proportion of pigs' cluster of differentiation (CD)45+ compared to the same amount of inorganic Se and lower organic Se addition. The proportion of CD45+ and CD4+ lymphocytes was higher (P < 0.05) in E3 group compared to the other groups. Higher (P < 0.05) proportion of CD21+ lymphocytes were measured in the E2 and E3 groups compared with the other groups. The highest (P < 0.01) activity of glutathione peroxidase (GSH-Px) in pig erythrocytes was observed in the E3 group, while higher (P < 0.05) activity of glutathione reductase (GR) was in all experimental groups related to the control one. A dietary addition of 0.5 mg/kg DM of organic Se in combination with zeolite (0.2% DM) has increased (P < 0.05) Se deposition in liver, muscle, and blood, compared to the dietary addition of 0.3 mg/kg DM of the organic Se.